Effects of onclansetron and Granisetron on postoperative nausea and vomiting in adult patients undergoing laparoscopic cholecystectomy - Bestas, Azize; Onal, Selami Ates; Bayar, Mustafa Kemal; Yidirim, Asli; Aygen, Erhan (Elsevier, 2007)
Background: Postoperative nausea and vomiting (PONV) are common and potentially distressing adverse events (AEs) associated with surgery and anesthesia. In patients undergoing laparoscopic cholecystectomy (LC) without antiernetic prophylaxis, the incidence of PONV can be as high as 72%. Objective: The aim of this study was to investigate the prophylactic antiemetic effects of ondansetron and granisetron in patients undergoing LC when these agents are administered before the end of surgery. Methods: Patients classified by the American Society of Anesthesiologist's physical status as I or 11 who were scheduled for elective LC were included in this randomized, double-blind, placebo-controlled study. Anesthesia was induced with thiopental 5 mg/kg and fentanyl 2 mu g/kg, and was maintained with isoflurane 1% to 3% in 50% oxygen and 50% nitrous oxide and fentanyl as needed. Approximately 20 to 30 minutes before the end of the surgery, the patients randomly received either IV ondansetron 100 mu g/kg (group 0), IV granisetron 40 mu g/kg (group G), or normal saline (group P). Plasma levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were determined preoperatively and 24 hours postoperatively. The patients were observed for 24 hours for PONV and other possible AEs. Postoperative pain intensity was determined using a 10-cm visual analogue scale. Four-point satisfaction scores were determined at 24 hours. Results: Ninety patients (69 women, 21 men) participated in the study. Demographic characteristics and operative data (duration of surgery and anesthesia and amount of intraoperative fentanyl) were similar in the 3 groups. The only AE reported by patients during the 24-hour observation period was nonsevere headache. The number of patients experiencing headache was similar in group P, group 0, and group G (10 [33%] patients, 6 [20%1, and 10 [33%], respectively). No significant changes were found in presurgical and postsurgical plasma levels of ALT and AST in any group. The mean (SD) satisfaction scores in group 0 and group G (3.0 [0.4] and 3.0 [0.61, respectively) were significantly higher than those in group P (2.5 [0.5]; both, P < 0.01). Immediately after surgery (period 0), significantly more patients in the placebo group (21 [70%]) experienced PONV compared with those in the ondansetron group (9 [30%1; P < 0.05) and the granisetron group (7 [23%]; P < 0.01). During the 24-hour observation period, a significantly greater number of patients in group P (18 [60%]) required a single dose of a rescue antiemetic drug compared with those in groups 0 and G (9 (30%] and 6 [20%], respectively; both, P < 0.01). Conclusions: Patients administered ondansetron 100 mu g/kg or granisetron 40 mu g/kg 20 to 30 minutes before the end of LC had significantly higher PONV control during the 24-hour postoperative observation period than patients receiving placebo. However, there were no significant differences between the active treatment groups in the incidence of PONV, patient satisfaction, or AEs.
Keywords: laparoscopic cholecystectomy; postoperative nausea and vomiting; ondansetron; granisetron